Enhancers and tools to improve luxury customer experience: hotel managers’ perspective - Veríssimo, M. (2015)
This study aims to explore how luxury hotels create hospitality experiences in order to examine consistency of manager’s statements. To this end, the study included a literature review to understand the major approaches used in creating customer experiences. Following this, thirty in-depth interviews were prepared and carried out with thirty international luxury hotel managers in both Brazil and Portugal. The findings reveal that personalized service, brand image, service quality, client contact and adaptation of services are enhancers of customer experience in luxury hotels. These enhancers together with gastronomy, decoration, spa & wellness, staff and social networks are the most mentioned elements, confirming efforts of hotels to integrate experiences as an important role for hospitality industry. As far as one knows, this is the first attempt to explore the perspectives of luxury hotel managers’ in creating customer experience using in-depth interview approach and content analysis.